Strategic Development of Halal Tourism Area in Samas BeachSrigading Village- Sanden- Bantul - Ansori, Sa’ban; Setiyartiti, Lilies (Universitas Muhammadiyah Yogyakarta, 2020)
This research aims to analyze the strategic development of tourism in Samas Beach, Srigading Village, Sanden Sub-District, Bantul as halal tourism. The analysis is obtained by identifying internal factor and external factor of Samas Beach. Internal factor consists of strength and weakness of development halal tourism. While external factors consists of opportunity factor and threat in tourism management. Besides, this research used performance components and importance analysis approach (IPA) to find out what are important and needed by visitor in enjoying halal tourism. The results suggest that the management must increase supporting facilities for visitor to pray according by SWOT method. This is important because in the development of Islamic tourism must pay attention to the cleanliness and ease of visitors to worship.